HUBUNGAN PENGETAHUAN DENGAN PERILAKU HIGIENE PENJAMAH MAKANAN DI INSTALASI GIZI RSUD DR. SOESELO SLAWI - Indriany, Dwi Putri (Jurnal Gizi dan Pangan Soedirman, 2018)
Food management in hospital where hygiene and sanitarian become basic principles in nutrition installation and support patients healing process. The research aims to determine the correlation between knowledge of food handlers and the behavior of food handlers in nutrition installation of RSUD dr. Soeselo Slawi. This quantitative research uses a cross sectional approach. The research subjects were food handlers in the Nutrition Installation of RSUD dr. Soeselo Slawi with total 23 people. The bivariate analysis used in the study was the Rank Spearman test. The results of the study indicate that knowledge of food handlers in RSUD dr. Soeselo Slawi appertain to good 60,9% and good hygiene behavior 39,1%. The age characteristics of food handlers are mostly 40-49 years old with total 11 people, female 19 people, majority education level of high school or SMK 14 people, and length of work >10 years 16 people. the results of the Spearman rank test, p value 0,510 was obtained. because p value >0,05;  then H0 accepted, meaning there are no correlation between knowledge with hygiene behavior of food handler in nutrition installation at RSUD dr. soeselo slawi. Keywords : Knowledge, hygiene behavior, food handler, nutrition installation.